Studying the determinant factors leading to congenital heart disease in newborns - Mohammadhossein Arjmandnia; Mahsa Besharati; Sajad Rezvan (Wolters Kluwer Medknow Publications, 2018)
Context: Congenital heart disease (CHD) is an important cause of death during the 1st year of life and includes a special group of cardiac diseases that exist from birth. These conditions arise due to the abnormal development of an embryo's normal structures. Aims: A case-control study was conducted to investigate the determinant factors leading to CHD. Materials and Methods: All newborns who have been diagnosed with CHD upon echocardiography in 2013 were considered as cases. The number of samples required was randomly selected from the newborns who lacked CHD on cardiography. The mothers of both groups were handed the questionnaires. Statistical Analysis Used: SPSS 23 was employed to analyze the data. Results: A statistically significant association was seen between CHD and a positive family history (FH) (P < 0.001), consanguinity (P < 0.001), maternal diabetes (P = 0.004), the use of antiepileptics during the first 45 days of gestation (P = 0.002), and the mother's education status (P > 0.001). No significant association was observed between CHD in the newborn and the age below 20 and above 35 years and (P = 0.11), maternal body mass index (BMI) (P = 0.44), smoking during the first 45 days of gestation (P = 0.017), and maternal rheumatologic diseases (P = 0.4). Conclusions: Newborns are at a greater risk of having CHD born from mothers with a FH of CHD, from consanguineous marriages, history of diabetes, antiepileptic use, and lack of folic acid use. However, no significant associations were found between newborn CHD and maternal age, BMI, or cigarette smoking.